Marketing yourself - Dorene Ciletti (South-Western, 2004)
Marketing Yourself utilizes a marketing framework to drive the development of a self-marketing plan and portfolio. The plan is based on the analysis of the student's own marketable skills and abilities. Knowing how to sell yourself is key to succeeding in business today! In addition to helping students make real-world connections to begin networking with professionals, this text is also designed to help students with after-graduation goal setting that matches their interests and aptitudes to appropriate college or post-secondary education